Effects of Antimony and Continuous Gelatin Addition on Current Efficiency in the Hudson Bay Zinc Electrowinning Tankhouse - P. J. Merrin; G. Owusu; K. B. McTaggart (The Minerals, Metals and Materials Society, 1997)
"This study was conducted at Hudson Bay Mining and Smelting's zinc electrowinning tankhouse to determine the effects of varying levels of antimony and continuous gelatin addition on current efficiency. The levels of antimony and gelatin were varied from 0.012 to 0.030 mg/l and 0 to 10 mg/ll2 • 31 respectively, based on neutral ZnS04 electrolyte. A non-linear mathematical model relating current efficiency with antimony and gelatin was produced. The optimum operating point for gelatin was 6.5 mg/l. On the other hand the current efficiency increased with decreasing antimony levels. An interaction term between gelatin and antimony is present but is not significant enough to improve the ability of the tankhouse to handle purification upsets in antimony. Individually, the current efficiency was linear (decreasing) with antimony, and parabolic with gelatin concentration. However, at low antimony concentrations stripping of the cathode sheet was difficult. IntroductionThe zinc electrowinning tankhouse at Hudson Bay Mining and Smelting was designed in the 1930's and consists of 120 rows with each row containing ten cells. This system cascades acid from cell to cell In a row, with neutral zinc sulphate solution added to each cell through manually controlled spigots. Animal glue additions are made manually three times per day by operations personnel. The problem with this type of cell design and operation is that feed solution flows and composition can vary from cell to cell and from row to row due to the large number of manual control points. A new system which reduces the number of manual control points was designed and tested to determine if improvement in control of cell conditions would affect current efficiency. This system mixes spent acid, neutral ZnS04 electrolyte and reagents (gelatin, antimony and strontium carbonate) in a separate mix tank, ensuring that all cells receive a uniform feed solution. Gelatin was used in the test system instead of animal glue (which is presently used) because of the poor solubility and supply of industrial animal glue. The study reported here is the first in a series of experiments designed to justify the need to modify the present cascading cell feed system (Figure 1) to the proposed feed system (figure 2)."